Sebaran Vegetasi Bunga Edelweis di Kawasan Taman Nasional Kelimutu dengan Citra Lansat 8 TM - Siki, Theodosia Monika; Pani, Emilianus; Semiun, Chatarina Gradict (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
Edelweis (Anaphalis longifolia) is one of Indonesia's mountain vegetation that grows at an altitude of 1,000–2,000 meters above sea level and plays a role as a pioneer plant in volcanic soils. Anaphalis longifolia is one of the places in Kelimutu National Park, which spans altitudes of 1,000–1,731 meters above sea level. Using Landsat satellite imagery, the research aims to identify environmental factors influencing edelweis distribution. Data collection was conducted across six tracking routes: Moni, Wologai-Protelindo, Dedumudi, Niowula, Ratebeke, and Saga-Bukit Sokoria, combining field observations with the analysis of Landsat 8 imagery, elevation SHP, rock type SHP, and NDVI values. The results of the study show that the distribution of edelweis is most commonly found at an altitude of 1471-1599 meters above sea level. Meanwhile, the distribution of edelweis is at least at an altitude of 1114-1200 meters above sea level. The types of rocks in the Kelimutu National Park area are young volcanic rocks and the distribution of edelweis tends to be more abundant in areas with moderate NDVI values (0.25-0.35). Environmental factors such as temperature, humidity, sunlight intensity, soil pH, and wind speed play a role in the spread of Edelweis in Kelimutu National Park.